DIGITAL IDENTITY CONSTRUCTION OF MOESLEM UNIVERSITY STUDENTS IN ENGLISH CLASSROOM - Yanuar, Ivo Dinasta (English Review: Journal of English Education, 2025)
This research aims to explore the digital identity construction of Muslim university students learning English through social media and its impact on their offline identity in the English classroom. Digital identity involves the use of social media platforms to express oneself, including through usernames, profile pictures, personal information, and followers. Muslim students develop complex identities by blending local cultural and religious values with global influences, using social media to showcase their English language skills. This qualitative study utilized semi-structured interviews with eight university students who are active on social media. The findings highlight those Muslim students often navigate between local and global identities, striving to present a balanced image online that aligns with their religious and social values. Furthermore, the study reveals a significant contrast between the digital identity they project on social media and the more formal identity they adopt in academic contexts, such as the English classroom. This research underscores the complexities of managing multiple identities in the digital age.